1987
DOI: 10.1002/chin.198743025
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Atmospheric Sulfidation of Copper Single Crystals.

Abstract: (100), (110), and (111) single crystals of Cu and polycrystalline copper have been exposed to a controlled test atmosphere containing low concentrations of H2S, designed to simulate atmospheric sulfidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Table I. The In and Al are thought to form vacancy traps that could slow the sulfidation reaction by limiting the Cu permeability and thus influence the supply of Cu (9). Resistance changes in the meander lines were monitored, in-situ, as a function of exposure time to a 50 ppb H 2 S, 80% RH, air environment at 35ºC.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table I. The In and Al are thought to form vacancy traps that could slow the sulfidation reaction by limiting the Cu permeability and thus influence the supply of Cu (9). Resistance changes in the meander lines were monitored, in-situ, as a function of exposure time to a 50 ppb H 2 S, 80% RH, air environment at 35ºC.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms for this Cu 2 S growth is clearly more complex than the simple model proposed by Graedel [9] for atmospheric sulfidation of Cu single crystals.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Copper is widely used in a number of critical electrical applications, and the problem and study of copper corrosion is a major area of research [1][2][3][4][5][6][7][8]. Previous researchers have studied the sulfidation of copper using SO 2 and H 2 S gas and found that these reactants interact at the wateroxide interface, possibly at copper oxide grain boundaries [5,[9][10].…”
Section: Background On Copper Sulfidationmentioning
confidence: 99%
“…Previous researchers have studied the sulfidation of copper using SO 2 and H 2 S gas and found that these reactants interact at the wateroxide interface, possibly at copper oxide grain boundaries [5,[9][10]. Solid-state diffusion of copper through Cu 2 O is thought to control the nucleation and initial Cu 2 S island growth on Cu 2 O -in the case of exposure to H 2 S gas -and copper-sulfite and copper-sulfate formation -in the case of exposure to SO 2 gas [5][6]. Also, for both H 2 S and SO 2 exposure, the rate of sulfidation can be controlled by the supply of corroding gas to the surface [4][5][11][12].…”
Section: Background On Copper Sulfidationmentioning
confidence: 99%